Multimedia Technology and Its Application in Courseware Making - Wang, Pingshui; Ma, Qinjuan (IJRDO - Journal of Social Science and Humanities Research, 2018)
The multimedia technology is one of the most advanced information display technique in modern educational technology. It has been widely used in college education and teaching. It is also welcomed and favored by teachers and students for its diversity and information media integration, interactive and real-time. Based on a brief introduction to the basic concepts of multimedia technology, the paper introduces the basic elements of multimedia and their specific applications in multimedia courseware making